Effects of Bardoxolone Methyl on Hepatic Enzymes in Patients with Type 2 Diabetes Mellitus and Stage 4 CKD. Issue 1 (3rd September 2020) - Lewis, James H.; Jadoul, Michel; Block, Geoffrey A.; Chin, Melanie P.; Ferguson, Deborah A.; Goldsberry, Angie; Meyer, Colin J.; O'Grady, Megan; Pergola, Pablo E.; Reisman, Scott A.; Wigley, W. Christian; Chertow, Glenn M.
Abstract : In a multinational placebo‐controlled phase III clinical trial in 2, 185 patients with type 2 diabetes mellitus and stage 4 chronic kidney disease, treatment with the Nrf2 activator bardoxolone methyl increased estimated glomerular filtration rate, a measure of kidney function, but also resulted in increases in serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma glutamyl transferase. These increases in liver enzyme level(s) were maximal after 4 weeks of treatment and reversible, trending back toward baseline through week 48. Total bilirubin concentrations did not increase, and no cases met Hy's Law criteria, although two subjects had ALT concentrations that exceeded 10 × the upper limit of the population reference range leading to discontinuation of treatment. Animal and cell culture experiments suggested that the increases in ALT and AST induced by bardoxolone methyl may be related to its pharmacological activity. Bardoxolone methyl significantly induced the mRNA expression of ALT and AST isoforms in cultured cells. Expression of ALT and AST isoforms in liver and kidney also positively correlated with Nrf2 status in mice. Overall, these data suggest that the increases in ALT and AST observed clinically were, at least in part, related to the pharmacological induction of aminotransferases via Nrf2 activation, rather than to any intrinsic form of hepatotoxicity.